2022
DOI: 10.1002/ieam.4572
|View full text |Cite
|
Sign up to set email alerts
|

Refining our understanding of metal bioavailability in sediments using information from porewater: Application of a multimetal biotic ligand model as an extension of the equilibrium partitioning sediment benchmarks

Abstract: The equilibrium partitioning sediment benchmarks (ESBs) derived by the US Environmental Protection Agency (USEPA) in 2005 provide a mechanistic framework for understanding metal bioavailability in sediments by considering equilibrium partitioning (EqP) theory, which predicts that metal bioavailability in sediments is determined largely by partitioning to sediment particles. Factors that favor the partitioning of metals to sediment particles, such as the presence of acid volatile sulfide (AVS) and sediment orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The present study first identified the leachable additives of TPs in the pore water of sediment, which could better reflect the bioavailability of the released tire chemicals in the soil or sediments. 37,38 Moreover, previous studies focused only on the leaching process of heavy metals and PAHs and failed to quantify other organic compounds. 19,21,39 Considering that TPs contain a variety of additives, investigating only heavy metals and PAHs may lead to the main toxic compounds in the leachate being overlooked, resulting in the underestimation of the toxicity of leachate to organisms or microorganisms in the soil/sediment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study first identified the leachable additives of TPs in the pore water of sediment, which could better reflect the bioavailability of the released tire chemicals in the soil or sediments. 37,38 Moreover, previous studies focused only on the leaching process of heavy metals and PAHs and failed to quantify other organic compounds. 19,21,39 Considering that TPs contain a variety of additives, investigating only heavy metals and PAHs may lead to the main toxic compounds in the leachate being overlooked, resulting in the underestimation of the toxicity of leachate to organisms or microorganisms in the soil/sediment.…”
Section: Discussionmentioning
confidence: 99%
“…The main problem is that the measured additive concentrations may not represent the bioavailable concentrations in solid media due to the limitations of the extraction methods, such as acid-based extraction or high-temperature extraction, which may enhance the leaching process. The present study first identified the leachable additives of TPs in the pore water of sediment, which could better reflect the bioavailability of the released tire chemicals in the soil or sediments. , Moreover, previous studies focused only on the leaching process of heavy metals and PAHs and failed to quantify other organic compounds. ,, Considering that TPs contain a variety of additives, investigating only heavy metals and PAHs may lead to the main toxic compounds in the leachate being overlooked, resulting in the underestimation of the toxicity of leachate to organisms or microorganisms in the soil/sediment. This was confirmed by the positive linear relationships between the levels of six organic compounds (acetophenone, 4-methylaniline, benzothiazole, octadecyl acetate, N-cyclohexylfomamide, and dicyclohexylamine) in pore water and TP amendment in this study ( R = 0.58–0.94, P < 0.01, Table S8).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of calculated toxic units with bioassay results suggest that metal concentration data collected from peepers (in combination with other porewater parameters collected via centrifugation) may more accurately reflect organism exposures than metal concentrations and bioavailability parameter data collected via centrifugation (Santore, Toll, et al, 2021). These results suggest that the collection of metal concentration data via peepers may be very useful for understanding metal toxicity in sediment bioassays, even when other bioavailability parameters must be collected by another method, such as centrifugation.…”
Section: Discussionmentioning
confidence: 99%
“…One-to-one plots of compiled porewater chemistry data were created to show porewater chemical concentrations by the extraction method for each data source. Figures comparing BLM toxic units calculated using porewater metal concentrations data collected via centrifugation as well as peeper and organism survival from several bioassay studies created for a companion paper (Santore, Toll, et al, 2021) were also examined to address questions about the use of porewater data in an EqP context.…”
Section: Key Questions and Approachmentioning
confidence: 99%
See 1 more Smart Citation